PENGARUH EMOTIONAL INTELLIGENCE DAN FUTURE TIME PERSPECTIVE TERHADAP PILIHAN KARIER GURU PADA MAHASISWA PENDIDIKAN EKONOMI ANGKATAN 2022 UNIVERSITAS JAMBI - Yuanda, Femas; Muazza; Sri Dwijayanti, Novia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low tendency of education students to choose the teaching profession as their future career. The purpose of this study was to analyze the influence of Emotional Intelligence and Future Time Perspective on teacher career choice among the 2022 cohort of Economics Education students at Jambi University. This study employed a quantitative approach using an Ex Post Facto method. The population consisted of 85 students from the 2022 cohort of Economics Education at Jambi University. The sampling technique used was total sampling, in which the entire population was selected as the research sample. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis. The results showed that Emotional Intelligence had a positive and significant effect on teacher career choice. Future Time Perspective also had a positive and significant effect on teacher career choice. Simultaneously, Emotional Intelligence and Future Time Perspective had a positive and significant effect on teacher career choice, with an F-value of 7.908 and a significance value of 0.001 < 0.05. The coefficient of determination (R²) was 0.262, indicating that Emotional Intelligence and Future Time Perspective explained 26.2% of the variance in teacher career choice, while the remaining 73.8% was influenced by other factors outside the scope of this study. Therefore, the higher the students' Emotional Intelligence and Future Time Perspective, the greater their tendency to choose the teaching profession as a future career.